A connection between pre-mRNA splicing and the cell cycle in fission yeast: cdc28+ is allelic with prp8+ and encodes an RNA-dependent ATPase/helicase. - Lundgren, K (1996)
The fission-yeast gene cdc28+ was originally identified in a screen for temperature-sensitive mutants that exhibit a cell-division cycle arrest and was found to be required for mitosis. We undertook a study of this gene to understand more fully the general requirements for entry into mitosis. Cells carrying the conditional lethal cdc28-P8 mutation divide once and arrest in G2 after being shifted to the restrictive temperature. We cloned the cdc28+ gene by complementation of the temperature-sensitive growth arrest in cdc28-P8. DNA sequence analysis indicated that cdc28+ encodes a member of the DEAH-box family of putative RNA-dependent ATPases or helicases. The Cdc28 protein is most similar to the Prp2, Prp16, and Prp22 proteins from budding yeast, which are required for the splicing of mRNA precursors. Consistent with this similarity, the cdc28-P8 mutant accumulates unspliced precursors at the restrictive temperature. Independently, we isolated a temperature-sensitive pre-mRNA splicing mutant prp8-1 that exhibits a cell-cycle phenotype identical to that of cdc28-P8. We have shown that cdc28 and prp8 are allelic. These results suggest a connection between pre-mRNA splicing and progression through the cell cycle.